Female subjects in black and white: Race, psychoanalysis, feminism - Abel, Elizabeth; Christian, Barbara; Moglen, Helene (University of California Press, 1997)
This landmark collaboration between African American and white feminists goes to the heart of problems that have troubled feminist thinking for decades. Putting the racial dynamics of feminist interpretation center stage, these essays question such issues as the primacy of sexual difference, the universal nature of psychoanalytic categories, and the role of race in the formation of identity. They offer new ways of approaching African American texts and reframe our thinking about the contexts, discourses, and traditions of the American cultural landscape. Calling for the racialization of whiteness and claiming that psychoanalytic theory should make room for competing discourses of spirituality and diasporic consciousness, these essays give shape to the many stubborn incompatibilities―as well as the transformative possibilities―between white feminist and African American cultural formations. Bringing into conversation a range of psychoanalytic, feminist, and African-derived spiritual perspectives, these essays enact an inclusive politics of reading. Often explosive and always provocative, Female Subjects in Black and White models a new cross-racial feminism.
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; femmes* afro-américaines; féminismes noirs; littérature; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences humaines; états-unis; études littéraires

Les scénarios sexuels des jeunes adultes latino-américains de Montréal : l'impact de l'acculturation et du genre - Arroyo, Javiera (Université du Québec à Montréal, 1997)
Keywords: IREF; amériques; discipline; genre; identités LGBTQIA2+; mémoires/thèses; québec; régions géographiques; sciences humaines; sexologie; sexualité; thématiques

Excitable speech: A politics of the performance - Butler, Judith (Routledge, 1997)
‘When we claim to have been injured by language, what kind of claim do we make?’ - Judith Butler, Excitable Speech Excitable Speech is widely hailed as a tour de force and one of Judith Butler’s most important books. Examining in turn debates about hate speech, pornography and gayness within the US military, Butler argues that words can wound and linguistic violence is its own kind of violence. Yet she also argues that speech is ‘excitable’ and fluid, because its effects often are beyond the control of the speaker, shaped by fantasy, context and power structures. In a novel and courageous move, she urges caution concerning the use of legislation to restrict and censor speech, especially in cases where injurious language is taken up by aesthetic practices to diminish and oppose the injury, such as in rap and popular music. Although speech can insult and demean, it is also a form of recognition and may be used to talk back; injurious speech can reinforce power structures, but it can also repeat power in ways that separate language from its injurious power. Skillfully showing how language’s oppositional power resides in its insubordinate and dynamic nature and its capacity to appropriate and defuse words that usually wound, Butler also seeks to account for why some clearly hateful speech is taken to be iconic of free speech, while other forms are more easily submitted to censorship. In light of current debates between advocates of freedom of speech and ‘no platform’ and cancel culture, the message of Excitable Speech remains more relevant now than ever.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; performativité; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; états-unis

Le processus de reconstruction des réseaux sociaux des femmes immigrantes dans l’espace montréalais - Chicoine, Nathalie; Charbonneau, Johanne; Rose, Damaris; Ray, Brian (Recherches féministes, 1997)
Le processus d'émigration produit un profond bouleversement des liens interpersonnels. L'arrivée dans un nouveau pays oblige à une reconstruction souvent presque complète des réseaux de sociabilité et d'entraide. Par l'entremise de l'étude des communautés ethniques, des chercheurs et des chercheuses ont mis en évidence l'importance des affinités ethnoculturelles dans la création des réseaux personnels après l'arrivée dans un nouveau pays. Cependant, ces travaux se sont rarement attardés sur la reconstruction du processus même de création des réseaux à partir d'expériences individuelles. En 1996, notre équipe a réalisé une enquête auprès d'immigrantes d'origine latino-américaine, polonaise et indienne, arrivées à Montréal entre 1988 et 1991 et mères de jeunes enfants. À l'aide d'instruments d'enquête quantitatifs et qualitatifs, nous avons retracé l'histoire de la construction du réseau social de ces femmes depuis leur arrivée au pays, à travers l'analyse des événements familiaux, résidentiels et professionnels vécus au cours de ces années. Nous présentons ici une synthèse du processus de création des réseaux sociaux de ces femmes et analysons en particulier l'influence de certains facteurs sur ce processus tels que l'origine ethnique, la proximité résidentielle et le vécu d'événements particuliers.
Keywords: 1900-1999; 1990-1999; amériques; cours; discipline; environnement; femmes immigrantes; périodes historiques; québec; régions géographiques; réseau social; sciences humaines; soc1061; sociologie; thématiques

L'histoire des femmes : construction et déconstruction d'une mémoire sociale - Fahmy-Eid, Nadia (Sociologie et sociétés, 1997)
Cet article analyse le rapport entre la mémoire sociale des femmes et l'histoire féministe qui a vu le jour au cours des trente dernières années. L'hypothèse défendue ici est que mémoire et histoire s'alimentent réciproquement et qu'elles sont toutes deux le fruit d'un construit social. Toutes deux opèrent un tri dans le passé et l'ordonnent selon une perspective particulière. Toutes deux s'inscrivent dans des rapports de pouvoir, rapports qu'elles reflètent en partie, mais qu'elles contribuent également à interroger et à remettre en cause. C'est ainsi que la mémoire des femmes et l'histoire féministe se sont avérées des éléments importants de conscientisation et de changement social.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; mémoire culturelle; pratiques féministes; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

L’organisation du travail dans des groupes de femmes - Fournier, Danielle; Guberman, Nancy; Beeman, Jennifer; Gervais, Lise (Nouvelles pratiques sociales, 1997)
À partir des données préliminaires d'une recherche en cours sur la culture organisationnelle des groupes de femmes, nous verrons en quoi leurs valeurs et leurs pratiques organisationnelles pourraient apporter une contribution importante aux réflexions actuelles sur les transformations de l'organisation du travail. L'article qui suit se divise en trois sections traitant : 1) de la méthodologie de la recherche; 2) de l'organisation du travail dans les groupes, du contrôle sur le processus du travail et de l'humanisation des rapports de travail; 3) de certains paradoxes découlant de cette organisation du travail.
http://id.erudit.org/iderudit/301405ar
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; canada; discipline; groupes de femmes; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail; travail social

Visibles et Partenaires: recherches et pratiques féministes - Garceau, Marie-Luce (Reflets: Revue ontaroise d'intervention sociale et communautaire, 1997)
Visibles et Partenaires est un colloque sur les pratiques et les recherches féministes en milieu francophone qui s’est tenu les 8, 9 et 10 mai 1997 à l’Université Laurentienne, Sudbury. Cet événement mémorable a regroupé plus de deux cents femmes de toutes les régions de l’Ontario et d’ailleurs. Plus d’une cinquantaine de conférencières provenant des milieux communautaires, universitaires et professionnels ont pris la parole et échangé avec les participantes. Visibles et Partenaires a été une occasion unique d’analyser divers aspects de la réalité des Franco-Ontariennes. Les femmes présentes ont pu partager leurs points de vue, leurs expériences, leurs savoirs. De plus, ce colloque a permis le développement de partenariats stratégiques axés sur l’action et les changements sociaux. Ce numéro de Reflets est consacré à quelques-unes des conférences qui ont été présentées lors de ce colloque.
Keywords: 1900-1999; 1990-1999; OFDIG; amériques; construction du savoir; discipline; femmes*; francophonie; ontario; périodes historiques; recherche partenariale; ressource en ligne; régions géographiques; savoir féministe; sciences humaines; travail social; épistémologie

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
https://search.libraries.emory.edu/catalog/990005217790302486
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

Le Red light de Montréal - Proulx, Daniel (VLB éditeur, 1997)
"La légende du défunt quartier montréalais dit du "Red Light" vaut bien celle des Soho et Pigalle de ce monde. Prospères au début du siècle, les salles de jeux enfumées et les chambres sordides de nos bas-fonds deviennent dans les années trente les derniers refuges des damnés de la crise. La guerre venue, les entrepreneurs en plaisirs défendus font des affaires d'or, en attendant que l'armée s'en mêle. La guerre finie, le Red Light renaît en force. C'est alors que Pacifique Plante et Jean Drapeau entrent en scène et procèdent à l'épuration radicale de nos moeurs. Le rideau tombe sur notre quartier "réservé". Aujourd'hui, la "Main" n'est plus qu'un coin de rue, à l'intersection de Sainte-Catherine et de Saint-Laurent. Ni ses habitués ni les passants n'ont idée de son spectaculaire passé." – Quatrième de couverture
Section: 83 pages, [32] pages de planches : photographies en noir et blanc ; 23 cm.
Keywords: 1900-1999; amériques; canada; cours; discipline; his4860; histoire; histoire de la sexualité; histoire et politique; industrie du sexe; montréal; premier cycle; périodes historiques; québec; red light; régions géographiques; révolution tranquille; sciences humaines; sexualité; thématiques; travail; travail du sexe

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis